2005
DOI: 10.1007/bf02704206
|View full text |Cite
|
Sign up to set email alerts
|

Negative chemical pressure effects induced by Y substitution for Ca on the ‘exotic’ magnetic behavior of the spin-chain compound, Ca3Co2O6

Abstract: The magnetic behavior of a solid solution, Ca 3-x Y x Co 2 O 6 , based on an 'exotic' spin-chain compound, Ca 3 Co 2 O 6 , crystallizing in K 4 CdCl 6 -derived rhombohedral structure is investigated. Among the compositions investigated (x= 0.0, 0.3, 0.5, 0.75 and 1.0), single phase formation persists up to x= 0.75, with the elongation of the c-axis. The present investigations reveal that the temperature at which the 'so-called' 'partially disordered antiferromagnetic structure' sets in (which occurs at 24 K fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…In the spirit of the recent experimental demonstration of negative pressure in ferroelectrics, [40,41] we exploit the multicaloric effect under negative pressure and electric field.…”
Section: Multicaloric Effect Under Mechanical and Electric Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the spirit of the recent experimental demonstration of negative pressure in ferroelectrics, [40,41] we exploit the multicaloric effect under negative pressure and electric field.…”
Section: Multicaloric Effect Under Mechanical and Electric Fieldsmentioning
confidence: 99%
“…[40] In addition, recent experimental results demonstrated that negative pressure as low as -4 GPa can be realized by the transformation between a lower-density crystal structure and the perovskite phase in freestanding PbTiO 3 nanowires. [41] Although the elastic heating would probably exist even under negative pressure, its contribution is expected to be reduced in single crystals under lower pressure.…”
Section: Multicaloric Effect Under Mechanical and Electric Fieldsmentioning
confidence: 99%
“…With these motivations, we present the results of a systematic investigation of the series Ca 3x Gd x Co 2 O 6 through ac and dc magnetization, heat-capacity (C), and complex dielectric measurements down to 1.8K. Among various observations, the findings of emphasis are: (i) Gd substitution lowers T N only marginally with respect to that known for Y substitution [34]. There is a change in the magnetic moment behavior as well, as though the valence of CoI changes with Gd substitution; interestingly, this seems to change even for CoII site in the case of x= 0.7.…”
Section: Introductionmentioning
confidence: 99%
“…To show the evolution of these magnetization steps with F-doping clearly, three dashed lines near these steps are plotted in the gure. Different to the doping effect on Ca- 18 or Co-sites, 30 F-doping at the O-site does not obviously change the magnetization steps, and the position of the magnetization steps were almost the same for all the samples studied. Although F-doping has little inuence on the position of these magnetization steps, the magnetization value of each step decreases with the increase of F-doping content, as shown in Fig.…”
Section: Magnetic Propertiesmentioning
confidence: 68%
“…From the perspective of future applications, searching for an n-type Ca 3 Co 2 O 6 with a low resistivity is imperative. Furthermore, the investigations on the effect of substitution in the Ca 3 Co 2 O 6 system are mainly focused on the Co 10,17 or Ca sites, 18,19 and studies on the substitution effect at the O site have not been reported so far. To fully understand the element substitution effect on the physical properties of Ca 3 Co 2 O 6 , in this work the structural, magnetic and TE properties of F-doped Ca 3 Co 2 O 6 were systematically studied over a large F composition range (0 # x # 0.8).…”
Section: Introductionmentioning
confidence: 99%